Perspectives from Texas Faculty in Non-CACREP Programs. Issue 1 (1st January 2017) - Wilson, Angie D.; Robertson, Derek; Stark, Marcella D.; Trepal, Heather
Abstract : In this study we utilized phenomenological inquiry to explore the experiences of nine counselor educators working in programs that are not accredited by the Council for Accreditation of Counseling and Related Educational Programs (CACREP). Five themes emerged including: (a) professional identity and unity, (b) resources and necessary support from administration, (c) pride in current program, (d) state requirements versus CACREP requirements, and (e) mounting pressure. Implications and recommendations are discussed.